PENINGKATAN KEMAMPUAN MENGENAL HURUF PADA TEMA TANAMAN DI KELOMPOK B TK MARAQITTA’LIMAT TEMBENG PUTIK - Wahyuni, Sri; Sabahiyah, Sabahiyah; Hasanah, Niswatul; Hadi, Mashal; Humairo, Yunisa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to determine the increase in the ability to recognize letters on the theme of plants in group B of Maraqitta'limat Tembeng Putik Kindergarten by using letter card games. This research is classroom action research consisting of two cycles. Research stages include planning, implementation, observation and reflection. The research subjects were group B, totaling 15 children, consisting of 10 boys and 5 girls. Data collection methods through interviews, observation and documentation. The instrument used in this research was an observation sheet on the ability to recognize letters which consisted of four indicators, namely naming letter symbols, matching letter symbols, composing words, and showing letters. Data were analyzed using a percentage formula to determine classical completeness in each cycle. The results of the research show that letter card games can improve children's ability to recognize letters. This increase can be seen from the children's classical completeness in cycle I, namely 60%, then increasing to 86% in cycle II. This is because children are very enthusiastic and motivated in learning. Through playing letter cards, children become more responsive so that their ability to recognize letters increases.